Efektivitas Sistem Informasi Akademik (SIAKAD) dalam Mendukung Proses Pelayanan Mahasiswa Di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako - Istiqamah, Andi Nurul; Cisadane, Maharani Aulia; Kamasi, Jesika Julianti Natalia; Haryono, Dandan (Jurnal ADMINISTRATOR, 2024)
Based on the observations of researchers at the Faculty of Social and Political Sciences, Tadulako University, it was found that students encounter problems accessing the Academic Information System (SIAKAD). Students often face difficulties in managing their study plan cards and scheduling courses. The aim of this study is to determine the effectiveness of the Academic Information System (SIAKAD) in supporting student services at the Faculty of Social and Political Sciences, Tadulako University. This research employs a descriptive qualitative method. The data collection techniques used are literature review, observation, and interviews. The data analysis techniques utilized in this study are data condensation, data display, and conclusion drawing/verification. Based on the research findings, it was discovered that in the process of student services at the Faculty of Social and Political Sciences, Tadulako University, out of the five effectiveness indicators, three have been met: program understanding, timeliness, and tangible changes. However, the indicators of timeliness and goal achievement have not been fulfilled. In conclusion, the effectiveness of the Academic Information System (SIAKAD) in the student service process at the Faculty of Social and Political Sciences, Tadulako University, is not effective because the indicators of timeliness and goal achievement have not been met.